Activation of the NRF2 pathway and its impact on the prognosis of anaplastic glioma patients. (10th October 2014) - Kanamori, Masayuki; Higa, Tsuyoshi; Sonoda, Yukihiko; Murakami, Shohei; Dodo, Mina; Kitamura, Hiroshi; Taguchi, Keiko; Shibata, Tatsuhiro; Watanabe, Mika; Suzuki, Hiroyoshi; Shibahara, Ichiyo; Saito, Ryuta; et al.
Abstract: Background: Nuclear factor erythroid 2–related factor 2 (NRF2) plays pivotal roles in cytoprotection. We aimed at clarifying the contribution of the NRF2 pathway to malignant glioma pathology. Methods: NRF2 target gene expression and its association with prognosis were examined in 95 anaplastic gliomas with or without isocitrate dehydrogenase ( IDH ) 1/2 gene mutations and 52 glioblastomas. To explore mechanisms for the altered activity of the NRF2 pathway, we examined somatic mutations and expressions of the NRF2 gene and those encoding NRF2 regulators, Kelch-like ECH-associated protein 1 (KEAP1) and p62/SQSTSM. To clarify the functional interaction between IDH1 mutations and the NRF2 pathway, we introduced a mutant IDH1 to T98 glioblastoma-derived cells and examined the NRF2 activity in these cells. Results: NRF2 target genes were elevated in 13.7% and 32.7% of anaplastic gliomas and glioblastomas, respectively. Upregulation of NRF2 target genes correlated with poor prognosis in anaplastic gliomas but not in glioblastomas. Neither somatic mutations of NRF2 / KEAP1 nor dysregulated expression of KEAP1/p62 explained the increased expression of NRF2 target genes. In most cases of anaplastic glioma with mutated IDH1/2, NRF2 and its target genes were downregulated. This was reproducible in IDH1 R132H–expressing T98 cells. In minor cases of IDH1/2 -mutant anaplastic gliomas with increased expression of NRF2 target genes, the clinical outcomes were significantly poor. Conclusions: The NRF2 activity is increased in a significant proportion of malignant gliomas in general but decreased in the majority of IDH1/2 -mutant anaplastic gliomas. It is plausible that the NRF2 pathway plays an important role in tumor progression of anaplastic gliomas with IDH1/2 mutations.